How Entrepreneurship Education Can Help Student Thrive in the Digital Age? : The Implications of Creative and Innovative Learning - Maulida, Fita Hanan; Noviani, Leny; Sudarno, Sudarno (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to identify the essential entrepreneurial skills required for students to tackle challenges and capitalize on opportunities in the present circumstances. Additionally, it provides information on how educators can utilize technology to create conducive learning environments that enhance students’ entrepreneurial skills. This study employed a systematic literature review method adapted from PRISMA 2020 guidelines. Qualitative data collection techniques were employed, followed by thematic analysis for data interpretation. Studies were retrieved from the Scopus database that published between 2018 and 2023. The findings revealed three key aspects to enhance students’ skills: personal, interpersonal, and digital aspects. The personal aspect encompassed creativity and innovation, initiative, self-efficacy, and resilience, as well as risk-taking. The interpersonal aspect included leadership, effective communication, collaboration, networking, and a positive attitude. The digital aspect comprised digital awareness, digital literacy, digital content, digital communication, digital creativity, and digital critical thinking. The study also found that experiential learning and project-based learning have been widely used in entrepreneurship education. This indicated that the effectiveness of entrepreneurship education for students can be achieved through learning experiences, problem-solving, and practical applications in an entrepreneurial environment. By employing various creative, innovative, and technology-based teaching techniques, educators can capture students’ engagement and provide added value to their learning experience.